Hydrological pulse regulating the bacterial heterotrophic metabolism between Amazonian mainstems and floodplain lakes - Vidal, Luciana O.; Abril, Gwenäel; Artigas, Luiz F.; Melo, Michaela L.; Bernardes, Marcelo C.; Lobão, Lúcia M.; Reis, Mariana C.; Moreira-Turcq, Patrícia; Benedetti, Marc; Tornisielo, Valdemar L.; Roland, Fabio (Frontiers in Microbiology, 2015)
We evaluated in situ rates of bacterial carbon processing in Amazonian floodplain lakes and mainstems, during both high and low water phases (p < 0.05). Our results showed that Bacterial Production (BP) was lower and more variable than Bacterial Respiration (BR), determined as total respiration. Bacterial Carbon Demand (BCD) was mostly accounted by BR and presented the same pattern that BR in both water phases. Bacterial growth efficiency showed a wide range (0.2–23%) and low mean value of 3 and 6 %, (in high and low water respectively) suggesting that dissolved organic carbon (DOC) was mostly allocated to catabolic metabolism. However, BGE was regulated by BP in low water phase. Consequently, changes in BGE showed the same pattern that BP. In addition, the hydrological pulse effects on mainstems and floodplains lakes connectivity were found for BP and BGE in low water. Multiple correlation analyses revealed that indexes of organic matter quality (chlorophyll-a, N stable isotopes and C/N ratios) were the strongest seasonal drivers of bacterial carbon metabolism. Our work indicated that: (1) the bacterial metabolism was mostly driven by respiration in Amazonian aquatic ecosystems resulting in low BGE in either high and low water phase; (2) the hydrological pulse regulated